(untitled) (Quinto Sol, 2026)
This article presents the preliminary results of a pilot project carried out between April and November 2022 to introduce and evaluate imagineRio Narratives with teachers and educators active in the city of Rio de Janeiro. An open and free tool for writing map-based stories, the Narratives tool allows students to engage in the historical geography of Rio through the interactive atlas of the imagineRio platform. This article presents discussions on pedagogical proposals that use geolocation as a device for students to interact with geographic space, reporting the initial reception of teachers participating in the pilot project and the potential uses of Narratives in their teaching and learning methodologies.